Education and the labour market: Building bridges to the future - Lopes, Eliane Pereira (Seven Editora, 2024)
The article explores the intersection between the education system and the labor market, highlighting the need for adequate preparation of students for the professional demands of the twenty-first century. Through a comprehensive analysis, the essential skills that should be developed in basic and higher education, the importance of continuous training and the role of public policies in creating a favorable environment for employability are discussed. The article also addresses the influence of new technologies and the need for a flexible curriculum that adapts to the rapid changes in the job market. Through a literature review, four articles on the context of the theme were analyzed. DOI:https://doi.org/10.56238/sevened2024.015-010